2021
DOI: 10.3390/nu13103359
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Exercise, Screen Time, Fast Food Consumption, Alcohol, and Cigarette Smoking during the COVID-19 Pandemic among Adults in the United States

Abstract: Objective: To investigate the impact of the COVID-19 pandemic on multiple lifestyle changes among adults in the United States (USA). Methods: We conducted a survey, the Health, Ethnicity, and Pandemic (HEAP) Study, in October 2020 among USA adults. Participants were selected from the United States using 48 sampling strata, including age, race, ethnicity, education, and gender, and were asked to report five lifestyle behaviors (i.e., exercise time, screen time, fast-food meal consumption, alcohol drinking, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 19 publications
6
73
1
Order By: Relevance
“…Dube et al documented substantial reductions in restaurant dining in several countries (including Australia, Canada, Germany, Ireland, Mexico, and the United Kingdom) due to various lockdown policies ( Dube, Nhamo, & Chikodzi, 2021 ). In the U.S., a study that examined fast-food consumption more broadly found that the percentage of adults who reported eating fast-food at least three times per week decreased from 37.7% to 33.3% during the beginning of COVID-19 ( Chen et al, 2021 ). It is noteworthy that while there were reductions in fast-food consumption relative to prior to the pandemic, overall rates were still high with over half of participants reporting fast-food consumption in the past week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dube et al documented substantial reductions in restaurant dining in several countries (including Australia, Canada, Germany, Ireland, Mexico, and the United Kingdom) due to various lockdown policies ( Dube, Nhamo, & Chikodzi, 2021 ). In the U.S., a study that examined fast-food consumption more broadly found that the percentage of adults who reported eating fast-food at least three times per week decreased from 37.7% to 33.3% during the beginning of COVID-19 ( Chen et al, 2021 ). It is noteworthy that while there were reductions in fast-food consumption relative to prior to the pandemic, overall rates were still high with over half of participants reporting fast-food consumption in the past week.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while indoor dining in restaurants became restricted, other options such as drive-thru, takeout, and delivery from restaurants remained with some restaurants pivoting to more limited menus with the more popular and high-performing options. Some research has found reductions in frequent fast-food consumption (defined as 3 or more times per week) ( Chen et al, 2021 ). However, little is known about socioeconomically disadvantaged adults, particularly from racial/ethnic minority groups.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies conducted amid the Covid-19 pandemic associated sociodemographic and behavioral characteristics with changes in alcohol consumption and cigarette smoking. In the United States, adults between 18 and 44 years old presented a higher prevalence of increase in alcohol consumption, and those with a higher income had a lower prevalence of cigarette smoking compared to less wealthy individuals [ 43 ]. In France, being between 18 and 34 years old was associated with increased alcohol and cigarette consumption [ 10 ], while in Brazil, individuals with lower educational levels had a higher increase in the frequency of cigarette smoking [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic caused by the SARS-CoV-2 virus and the subsequent preventive actions to reduce the number of contagions (social distancing, lockdown, quarantines, lockout, etc.) modified the habits of the population [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and caused different physical, psychological, and social effects [ 20 , 21 , 22 , 23 , 24 , 25 ]. In the childhood and youth population, which already exhibited physical activity values below the general recommendations ahead of the pandemic [ 26 , 27 ], these events and policies further reduced physical activity levels and increased sedentary behaviour [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some extracurricular physical and sports practices were called off or limited during the first pandemic year, reducing even further the opportunities for physical exercise in children and adolescents [ 30 ]. In addition, dietary habits changed during this time, with generally increased intake and particularly higher consumption of ultra-processed products [ 14 , 19 , 31 ].…”
Section: Introductionmentioning
confidence: 99%